Seasonal Variation in Biomass, Abundance and Plant Length of Different Life Stages from Gracilaria cliftonii (Gracilariales, Rhodophyta) - Munoz, Julieta; Fewtrell, Jane; Fotedar, Ravi (Begell House Inc., 2012)
Gracilaria is the most importance source of raw material for the extraction of the polysaccharide agar. Despite its worldwide importance, few papers have addressed the effect of different life stages on the biomass and agar production. Gracilaria cliftonii Withell, Millar & Kraft (1994) has been identified as a potential species for aquaculture due to its high agar yield (> 60%). However, information related to seasonal variations in biomass and abundance of the species has not yet been determined. The present study reports the seasonality of biomass, abundance, occurrence and plant length variations of different life stages from G. cliftonii from Western Australia. The biomass and abundance of tetrasporophyte and carposporophyte stages of G. cliftonii in autumn was significantly higher (< 0.05) than other seasons, while the biomass of the vegetative stage was significantly higher in spring and summer. Biomass and abundance were found to be dependent on nitrate and nitrite concentration, while male biomass was dependant (< 0.05) on rainfall and osmolality. The present study provided new information on the phenology of Gracilaria from a different location of the world and demonstrates that variations in biomass, abundance and plant length of G. cliftonii are influenced by environmental parameters.